The Significance of Bioactive Compounds in The Complex Realm of Cardiovascular Complications - Chakraborty, Sreejita; Hussain, Adib; Nayak, Arabinda (Pharmacognosy Reviews)
Leading cause of morbidity and death globally, Cardiovascular Diseases (CVDs) call for sensible preventive and treatment plans. Recent studies have concentrated on bioactive chemicals originating from natural dietary sources like fruits, vegetables, herbs, and marine resources for their cardioprotective action. Key bioactive substances like flavonoids, polyphenols, omega-3 fatty acids, and phytosterols show notable health advantages by enhancing endothelial function, lowering oxidative stress, controlling inflammation, and so changing lipid metabolism. Notwithstanding encouraging results about their capacity to reduce the risks of hypertension and atherosclerosis, practical application of them still faces difficulties including varied bioavailability, individual response variations, and the necessity of regular dosages. This review emphasizes the need for thorough clinical studies to prove their safety and efficacy as well as the possibilities of bioactive substances as supplementary treatments for improving cardiovascular health.
Keywords: Bioactive compounds; Cardiovascular diseases; Oxidative stress; Health Benefits; Challenges and Opportunities